HORMONAL AND IMMUNOLOGICAL STUDIES IN DIFFERENT TRIMESTER OF PREGNANCY IN COWS - HARICHANDAN, P P; MOHANTY, D N; DAS, S; PATRA, B K (The Indian Journal of Animal Reproduction, 2023)
This investigation was carried out with an objective to study serum progesterone and total immunoglobulinlevels of cows in three different trimesters of pregnancy. A total of 10 pregnant cows were selected for theinvestigation besides 10 normal, healthy and non-pregnant cows at oestrus which were considered as controlgroup. Blood sample collected in each gestational stage and serum sample were estimated through kitssupplied by Crest Biosystems. The serum progesterone values (ng/ml) observed in first, second and thirdtrimester of pregnancy were 4.85 ± 1.5, 5.76 ± 0.46 and 4.75 ± 1.36 respectively. The cows at oestrus recordeda value of 0.88 ± 0.14 (ng/ml) for serum progesterone concentration. The analysis of variance revealed ahighly significant difference (p
Keywords: Cow; Pregnancy trimester; Total lmmunoglobulin; Progesterone profile